2013
DOI: 10.1038/onc.2012.628
|View full text |Cite
|
Sign up to set email alerts
|

The mitotic kinase Aurora-A promotes distant metastases by inducing epithelial-to-mesenchymal transition in ERα+ breast cancer cells

Abstract: In this study, we demonstrate that constitutive activation of Raf-1 oncogenic signaling induces stabilization and accumulation of Aurora-A mitotic kinase that ultimately drives the transition from an epithelial to a highly invasive mesenchymal phenotype in estrogen receptor α-positive (ERα+) breast cancer cells. The transition from an epithelial- to a mesenchymal-like phenotype was characterized by reduced expression of ERα, HER-2/Neu overexpression and loss of CD24 surface receptor (CD24 –/low). Importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
161
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(176 citation statements)
references
References 41 publications
14
161
0
1
Order By: Relevance
“…AURKA, as the centrosome-associated kinase, not only induced centrosome abnormality, but also promoted the development of epithelial-mesenchymal transition and stemness of tumor cells (30). In accordance with previous studies, our current study found that AURKA overexpression induced extra centrosomes and stemness development in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 81%
“…AURKA, as the centrosome-associated kinase, not only induced centrosome abnormality, but also promoted the development of epithelial-mesenchymal transition and stemness of tumor cells (30). In accordance with previous studies, our current study found that AURKA overexpression induced extra centrosomes and stemness development in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 81%
“…Based on these data, it seems that development of the mammalian brain and eye relies on a narrow range of PLK4 expression, with centrosome depletion and CA resulting in impaired growth due, at least in part, to mitotic defects. It is unclear whether PLK4-overexpression-driven CA results in similar phenotypes in mammary stem cells; however, tumor cells from xenografts of MCF-7 cells with constitutively active Raf-1 oncoprotein (MCF-7 ΔRaf-1 cells) exhibit mesenchymal phenotype along with upregulated AURKA expression and robust phosphorylation only in CD24 −/low (vs. CD24 + ) cells, which also exhibit CA, so AURKA may promote stem-like features through CA (D'Assoro, et al 2014). More research is needed to clarify how PLK4-overexpression-induced CA impacts mammary stem cell division and the implications for breast tumorigenesis.…”
Section: Centrosome Amplification and Breast Tumorigenesismentioning
confidence: 99%
“…AURKA knockdown increases taxane chemosensitivity and hinders in vivo tumorigenesis (Hata et al, 2005). A recent study revealed a positive role of AURKA in promoting EMT in breast cancer and pancreatic cancer through experiments using the AURKA inhibitor Alisertib (also known as MLN8237); however, the molecular mechanism by which AURKA promotes EMT remains unclear (D'Assoro et al, 2014;Wang et al, 2015). In this study, we identified a crucial role of AURKA in promoting EMT in cells and in vivo.…”
Section: Introductionmentioning
confidence: 99%